When grit leads to success: The role of individual entrepreneurial orientation - Hussein-Elhakim Al Issa (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
Successful enterprise has been related to numerous characteristics including entrepreneurial orientation. The current study aims to examine the influence of individual entrepreneurial orientation and grit dimensions on entrepreneurial success. The potential mediating role of consistency of interest and perseverance of effort, on the relationship between entrepreneurial orientation and success, was also explored. Survey data were collected in Tripoli, Libya from entrepreneurs during the current economic downturn and crisis. The data from the usable 147 responses was analyzed using partial least squares structural equation modelling. The statistical results revealed a significant relationship between the individual entrepreneurial orientation, consistency of interest, and perseverance of effort, with the dependent variable, entrepreneurial success. The dimensions of grit were also found to mediate the relationship between entrepreneurial orientation and success. The cross-sectional nature of the study and the smaller sample size make the findings difficult to generalize. Verification of the significance of success predictors can unravel concerns about the low rate of established and nascent businesses despite the presence of opportunities and positive perception of entrepreneurship. The study of grit dimensions as a mediator between the individual entrepreneurial orientation and success is unprecedented.
Keywords: L26; 650; individual entrepreneurial orientation; entrepreneurial success; grit; consistency of interest; perseverance of effort; crisis